Mesiodens in a permanent and mixed dentition - A. I. Markova; I. M. Todua; R. A. Bokova; Sh. M. Solimanov; Sh. A. Nazhmudino; A. B. Adzhieva (LLC "Endo Press", 2020)
Supernumerary teeth are considered one of the most significant tooth abnormalities in the initial and early stages of mixed and primary dentition. They are of great importance to dentists and parents because of the problems that they can cause. Mesiodens is one of the supernumerary teeth. Early recognition and diagnosis of this anomaly is important to prevent further complications. The aim of this review is to clarify the literature regarding the clinical, radiological aspects, treatment, and complications associated with mesiodens in primary and mixed teeth.